A Comparative Analysis of Financial Professionals' Perception of the Level of Graduating Business Student Retirement Planning Familiarity, Motivation, and Preparedness. Issue 2 (September 2015) - Power, Mark; Hobbs, Jonathan M.
Abstract Academic, government, employer, and individual interest in personal financial literacy have mushroomed as financial decision making has become more complex, costly, and less paternalistic. Financial illiteracy in America manifests in many ways, including low levels of personal saving, high levels of personal debt, negative financial wealth, a decline in standard of living, and increased demand on social safety networks. For college students, of particular concern is the high level of public and private debt accrued while working toward a degree. It is important to understand how prepared households are for retirement planning decisions and which factors can improve their preparedness. We show that financial education is impactful in reducing financial illiteracy, and provides evidence that taking a personal risk management and insurance course helps to prepare college students to make retirement decisions. Second, we provide evidence that life stage explains differences (similarities) in how professionals self‐rate the importance, familiarity, and motivation to plan and save for retirement versus their opinion on how vital the questions should be to students. Finally, additional evidence is provided showing that demographic characteristics explain differences in the importance and motivation to plan and save for retirement and in the familiarity that respondents have with retirement planning and saving products.